2013
DOI: 10.1190/int-2013-0026.1
|View full text |Cite
|
Sign up to set email alerts
|

Seismic characterization of a Mississippi Lime resource play in Osage County, Oklahoma, USA

Abstract: With the advent of horizontal drilling and hydraulic fracturing in the Midcontinent, USA, fields once thought to be exhausted are now experiencing renewed exploitation. However, traditional Midcontinent seismic analysis techniques no longer provide satisfactory reservoir characterization for these unconventional plays; new seismic analysis methods are needed to properly characterize these radically innovative play concepts. Time processing and filtering is applied to a raw 3D seismic data set from Osage County… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…This migration-SOF-demigration process is iterated three times, providing acceptable convergence of the least-squares misfit function (see Guo et al [2012] for such analysis). We observed that in Figure 10a, a low-amplitude strip exists in Dowdell et al, 2013) showing (a) a vertical line through the prestack timemigrated data and (b) a horizon slice along the top Ellenburger through coherence volume. The coherence image is particularly noisy.…”
Section: Applicationmentioning
confidence: 96%
See 1 more Smart Citation
“…This migration-SOF-demigration process is iterated three times, providing acceptable convergence of the least-squares misfit function (see Guo et al [2012] for such analysis). We observed that in Figure 10a, a low-amplitude strip exists in Dowdell et al, 2013) showing (a) a vertical line through the prestack timemigrated data and (b) a horizon slice along the top Ellenburger through coherence volume. The coherence image is particularly noisy.…”
Section: Applicationmentioning
confidence: 96%
“…The merged 15-fold surveys cover an area of 207 km 2 (80 mi 2 ). Initially, the data were processed with a conventional workflow that worked very well on an Osage Co., OK, 60-fold Mississippi Lime survey acquired in 2012 (Dowdell et al, 2013). The resulting images were strongly contaminated by the acquisition footprint (Figure 7), much of it due to highly aliased broadband groundroll.…”
Section: Applicationmentioning
confidence: 99%
“…The objective is to map tripolite (high-porosity, diagenetically altered chert) that forms reservoir sweet spots as well as natural fractures that can provide conduits through the otherwise tight (usually underlying) fractured chert (Dowdell et al, 2013). In this survey from Kansas, there is also a spiculitic (from sponges) component to the chert (the Cowley Formation).…”
Section: Interpretation / February 2015 Sb7mentioning
confidence: 99%